Issue Fatigue Over the Course of the Covid-19 Pandemic - Annemarie Wiedicke; Paula Stehr; Constanze Rossmann (University of Zurich, IKMZ - Department of Communication and Media Research, 2023)
During times of uncertainty, such as the Covid-19 pandemic, people tend to cope through active information seeking. However, information overexposure can also lead to issue fatigue, a state in which recipients are increasingly annoyed and may actively avoid further information on this specific issue. Against this backdrop, we were interested in (1) whether people in Germany have experienced Covid-19 related issue fatigue over the course of the pandemic, (2) and if so, how Covid-19 information behaviour may have contributed to it, and (3) to what extent TV news coverage exhibits characteristics that are considered to contribute to recipients' issue fatigue. To address these questions, we combined a two-wave panel survey (2020) and a cross-sectional survey (2021) of the German population with a quantitative content analysis of Covid-19 related TV news (2020 and 2021). The results show an increase in issue fatigue over time. However, there was no evidence indicating that people's Covid-19 information behaviour has contributed to this. Rather, both information seeking and the reception of public TV news were negatively related to issue fatigue. Notably, TV news coverage showed characteristics that are considered determinants of issue fatigue, including its extent and an overall ambivalent-to-negative tone.